Green approach for the recovery of secondary metabolites from the roots of Nardostachys Jatamansi (D. Don) DC using microwave radiations: Process optimization and anti-alzheimer evaluation - Arya, Ashwani; Chahal, Rubal; Almutairi, Mikhlid H.; Kaushik, Deepak; Aleya, Lotfi; Kamel, Mohamed; Abdel-Daim, Mohamed M.; Mittal, Vineet (Frontiers in Plant Science, 2022)
Nardostachys jatamansi (D. Don) DC is a highly valued medicinal herb that has been used in traditional medicinal system for its remedial effects.Owing to over exploitation and unethical trade of N. jatamansi, the accelerating global demand of the herbal products from this plant cannot be satisfied by conventional extraction approach. In view of progressive demand and incredible biological potential of herb, the present research was designed to optimize various extraction parameters for microwave-assisted extraction (MAE). The extracts obtained from the traditional and green approach were also assessed for the recovery of secondary metabolites and anti-alzheimer potential. Various parameters like microwave power, temperature and time of irradiation were optimized for MAE using Box Behkhen Design (BBD) The scanning electron microscopy of different plant samples were also done to observe the effect of microwave radiations. Further, the metabolite profiling of different extracts was also done by gas chromatography-mass spectrometry (GC-MS) analysis. Also the different behavioral and biochemical parameters along with acetylcholinesterase (AChE) inhibitory potential were assessed to evaluate the anti-alzheimer potential. Optimized parameters for MAE were found to be as microwave power 187.04 watt, temperature 90°C and irradiation time 20 min. The extract yield in MAE significantly enhanced as compared to the conventional method. Also, the total phenolic content and total flavonoid content (TFC) were improved pointedly from 32.13 ± 0.55 to 72.83 ± 1.1 mg of GAE/g of extract and 21.7 ± 0.85 to 39.21 ± 0.7 mg of RUE/g of extract respectively. Later, the GC-MS analysis of various extracts confirmed the enhancement in concentration of various sesquiterpenes like jatamansone, spirojatamol, valerenal, valeric acid, globulol, nootkatone and steroidal compounds such as sitosterol, ergosterol and stigmastanone etc. in optimized extract. A significant improvement in anti-alzheimer potential was also observed owing to the better concentration of secondary metabolites in the optimized microwave extract. From the current findings, it could be concluded that the MAE could be a successful and green alternative for the extraction and recovery of secondary metabolites from the selected medicinal herb.